The silence on climate change by accounting's top journals - Brown, Alistair; Pignatel, I.; Hanoteau, J.; Paranque, B. (Common Ground Publishing, 2009)
The purpose of this article is to examine the contribution made to climate change issues by the elite ‘top 5’ international accounting journals of Accounting Organizations and Society, Contemporary Accounting Research, Journal of Accounting and Economics, Journal of Accounting Research and The Accounting Review, for the period 2000-2005. The main methodological approach used in this study is textual analysis which attempts to discern the underlying climate change discourse and ideology of these ‘high quality’ accounting journals’ accounting articles. The contribution made by these ‘top 5’ accounting journals amounts to nine journal articles and three research notes. While the articles of Herbohn (2005) and Gray (2002) break the pattern of ‘top 5’ ritualistic capital market based climate change accounting publications, the absence of a contemporary wide-ranging number of environmental accounting research articles by these ‘high quality’ journals underlies the ‘top 5’ accounting academia’s complicity in the status quo of denial about the planet’s problems.